PENGARUH FAKTOR-FAKTOR FUNDAMENTAL KE UANGAN TERHADAP HARGA SAHAM PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BEI - Firda Silviyatul Husnia (Manajemen Bisnis, 2015)
This study was conducted to determine the effect of factors such as financial fundamentals Earning Per Share (EPS), Return On Assets (ROA), Net Profit Margin (NPM), Debt To Equity Ratio (DER), and Current Ratio (CR) of the company and real property estate listed in Indonesia Stock Exchange during the period 2008-2013. The sampling technique used purposive sampling with a sample of five companies. Variables include the Earning Per Share (EPS), return on assets (ROA), Net Profit Margin (NPM), Debt To Equity Ratio (DER), and Current Ratio (CR) as the independent variable and stock price as dependent variables. Data were analyzed using descriptive statistical analysis and multiple linear regression analysis. The results of this study indicate that the simultaneous regression test (Test F), shows that the Earning Per Share (EPS), return on assets (ROA), Net Profit Margin (NPM), Debt To Equity Ratio (DER), and Current Ratio (CR ) simultaneously  influence the stock prices of five companies that were visited. While partial regression test (t test) showed that the variable EPS, ROA, NPM and CR partial effect, whereas the variable DER has no partial effect on stock prices.